Do heart rate variability is relationed to endurance performance in female futsal players? - Julio Cesar Barbosa de Lima Pinto; Radamés Maciel Vitor Medeiros; Arnaldo Luis Mortatti; Fábio Yuzo Nakamura; Leonardo de Sousa Fortes; Daniel Gomes da Silva Machado; André Igor Fonteles (Universidade Federal de Santa Catarina, 2021)
The study aimed to verify the correlation between resting heart rate variability (HRVrest) and endurance performance in female futsal players, as well as to evaluate the reliability of this parasympathetic autonomic marker. A total of 16 female futsal players (age: 22 ± 3 years; VO2max: 42.3 ± 2.0 ml.kg-1.min-1) were evaluated during the first week of preseason training. Vagal modulation was evaluated from the HRVrest (i.e., log-transformed root mean square of successive R-R interval differences - Ln-RMSSD) for two consecutive days, while endurance performance was evaluated by the Yo-Yo Intermittent Recovery Test, Level 1 (Yo-Yo IR1). Pearson correlation was used to analyze the relationship between the variables. Strong correlation between the HRVrest index and endurance performance (r = 0.643; p = 0.007). Reliability was tested through the intraclass correlation coefficient, coefficient of variation (CV), and Bland-Altman analysis of the agreement. Furthermore, acceptable repeatability of HRVrest, but with great inter-subject variability (ICC = 0.670, 95%CI = 0.056-0.885, CV = 15.8%). The current study demonstrated a strong correlation between Ln-RMSSD and endurance performance, and despite the acceptable values of intrasubject reliability, HRVrest presented high inter-individual variability in female futsal players.